The Kangaroo Method Treatment Effectively Increases Low Newborn Weight (LBW) - Ari Kusmiwiyati (ARTERI : Jurnal Ilmu Kesehatan, 2023)
Background: LBW is one of the highest causes of neonatal death in developing countries. Indonesia ranks 8th based on the number of neonatal deaths per year according to WHO data. The Infant Mortality Rate (IMR) in Indonesia in 2019 was 72,000 babies and 19% of deaths were caused by premature and LBW babies. Many cases of death in LBW occur because babies who experience LBW are susceptible to exposure to nosocomial infections, tend to have co-morbidities and the body's organs are not ready to face the external environment and case management is not optimal. One cheap and easy solution that can be done when a baby has LBW is to apply the Kangaroo Method of Care (PMK). Methods: The design used in this study is Traditional Literature Review obtained from 3 data based, namely Pubmed, Science Direct, Google Scholar using inclusion and exclusion criteria. Keywords used in the literature search: Kangaroo-Mother care Method and Weight Gain and Infant, Low Birth Weight. Of the 14 journals found, the journal selection was carried out using PICOS, then analyzed one by one with the results of 12 journals from Google Scholar data and 2 journals from PubMed data.Results: The results of the article review found that the Kangaroo Method Treatment can be carried out in LBW from the age of 0 days with a minimum administration time of 1 hour a day, the implementation must be in accordance with the readiness of the mother and baby, and the maximum application can increase the baby's weight. Conclusion: Kangaroo-Mother care has been proven to be effective in increasing body weight in LBW babies so that FMD can be intervened in LBW babies